Estetika Tri Mandala Dalam Komposisi Baru Pasupati: Strategi Pengembangan Wacana Keindahan dalam Karawitan - Ardana, I Ketut Ketut; Consentta, Maria Goretti Indah Della (Institut Seni Indonesia Yogyakarta, 2022)
Aesthetics has an important role in determining the weight of karawitan. Aesthetics can also justify the creation of a composition. Naturally, if in the assessment of composition is always influenced by aesthetic factors to determine the high and low value of karawitan. However, aesthetic perspective also needs to be a reference to show the renewal of a karawitan. It's a form of creativity in art. One of the conceptions that can give aesthetic harmony in karawitan composition is the concept of tri mandala. Tri mandala is a three-dimensional philosophical concept of harmony that is usually a reference in the field of architecture to build sacred places, residences, and even traditional markets in Bali. Through the concept of Tri mandala, a karawitan harmony system that was originally oriented to the second dimension became developed into the third dimension. Therefore, the topic of tri mandala aesthetics in pasupati composition needs to be researched so that it can result in a new aesthetic point of view in karawitan. This topic is a type of qualitative research that is studied with several stages, namely: observation, consoralization, composite realization. The results showed that tri mandala renews the aesthetic value of a karawitan composition. The renewal is represented in a system of harmony, structure, and meaning. The connection of the three with the tri mandala is the third dimension. Everything refers to the power of three, the harmony of three, part three, and the meaning of three in the symbolization of the three realms namely, bhur, bwah, and swah.